Letters to the church : a survey of Hebrews and the General Epistles - Jobes, Karen H. (Grand Rapids, Mich. : Zondervan, 2011)
"Respected New Testament scholar Karen Jobes explores the cultural and theological background of Hebrews and the general epistles (James through Jude) in this rich commentary. Writing from an evangelical perspective, Jobes addresses issues of historical relevance as well as how these ancient books connect with Christian faith and practice today. Letters to the Church includes: historical background for each book focusing on authorship, genre, date, and content; an exploration of the major themes in each book and detailed commentary on key passages; boxes with chapter goals, outlines, challenges, and significant verses; sidebars addressing difficult passages or ideas; maps, photographs, charts, and definitions; questions for discussion, reflection, and testing; a comparison of the teachings about Christ in each of the letters. Pastors, professors, students, and laypeople interested in deeper biblical study will find this an invaluable resource that offers well-researched commentary in an accessible, spiritually meaningful form" -- Publisher description.
Includes bibliographical references and indexes.
Keywords: Bible. -- Textbooks; Bible. -- Textbooks